Q&A with Holmes Rolston: Life persists in the midst of its perpetual perishing - Rolston, Holmes, 1932-2025, author; Dodge, Jeff, author; Source, Colorado State University, publisher (Colorado State University. Libraries, 2020)
Life persists in the midst of its perpetual perishing. The coronavirus brings novel experience of staying apart and keeping life safe together when finding a pasqueflower blooming at Easter. This minute critter has played havoc with mighty humans. Nature is still there, wild nature, both predictable and chaotic. The devastating virus brings struggle and promising opportunities for more caring, love, and solidarity in our human communities. Death is not the last word.

This interview may also be found online at: https://libarts.source.colostate.edu/qa-with-holmes-rolston-life-persists-in-the-midst-of-its-perpetual-perishing/.
Life persists in the midst of its perpetual perishing
Published in Source, Colorado State University online newsletter. May 28, 2020.
Keywords: coronavirus; perpetual perishing; solidarity; caring; love; predictable nature; chaotic nature; struggle in evolution; conflict and resolution; life and death; novel opportunities